Intervención psicopedagógica basada en la gimnasia cerebral para estimular la atención y memoria en una estudiante con discapacidad intelectual moderada de tercer año de bachillerato de la Unidad Educativa Pio Jaramillo Alvarado, 2021 – 2022. - Macas Cuenca, Erika Lizbeth (2023)
The present curricular integration work denominated: Psychopedagogical intervention based on brain gymnastics to stimulate attention and memory in a student with moderate intellectual disability in the third year of high school of the Pio Jaramillo Alvarado Educational Unit, 2021 - 2022, had as a general objective: To Implement the psychopedagogical intervention based on brain gymnastics to stimulate attention and memory in a student with moderate intellectual disability; the study was based on a qualitative, descriptive, cross-sectional approach and case study method; As techniques, the semi-structured interview, the Neuropsi Test : Attention and Memory, the observation sheet, and the learning achievement sheet were used for the collection of information . The results obtained indicate that one of the four interviewees considers that brain gymnastics could stimulate the attention and memory of the student, while three of them state that they have no knowledge about whether or not it could contribute to the stimulation of attention and memory of the student, likewise, it was found that the student presents levels of severe alteration in both attention and memory, in this sense, a brain gym exercise guide was designed, structured by a total of 10 workshops and different exercises selected to stimulate the attention and memory of the student with intellectual disabilities; At the beginning of the application of the psychopedagogical intervention, the student was reluctant to carry out the exercises, and presented difficulties carrying them out. During the process, she began to show greater motivation and availability to carry out the proposed exercises; finally, through the learning achievement sheet both in the evaluation of the performance of the exercise and at the discretion of the tutor teacher, the student reached a medium level of achievement. It is concluded that only one of the 4 teachers interviewed maintains the criteria that brain gymnastics would stimulate the attention and memory of the student, the case study with moderate intellectual disability presents levels of severe alteration in attention and memory therefore a proposal for psychopedagogical intervention as designed and applied for which effectiveness is minimal. Keywords: Intellectual disability, brain gym, cognitive stimulation, memory in intellectual disability.